Music education in the twenty-first century: a psychological perspective - Hargreaves, David; Marshall, N.; North, Adrian (Cambridge University Press, 2003)
Starting from Hargreaves’ (1986a) review of the relationship between developmental psychology and music education, we characterise the mid-1980s as a point at which the different main strands of music psychology – cognitive, developmental, and social – began to unfold. We move to the present day and beyond, suggesting that a major change has been the incorporation of a social perspective: it may now make more sense to talk about the developmental social psychology of music and music education. Four levels of social influence are distinguished – the individual, the interpersonal, the institutional,and the cultural – and we suggest that the concept of identity may enable explanations of social influence at the individual level. We review some research on musical style sensitivity as an exemplar of this general approach, and conclude by applying the social–cultural perspective to current developments in music education. This gives rise to two new conceptual models: of the opportunities that are offered by music education in the twenty-first century, and the outcomes that might be derived from it.